2011
DOI: 10.1073/pnas.1018687108
|View full text |Cite
|
Sign up to set email alerts
|

Boundary cap cells are peripheral nervous system stem cells that can be redirected into central nervous system lineages

Abstract: Boundary cap cells (BC), which express the transcription factor Krox20, participate in the formation of the boundary between the central nervous system and the peripheral nervous system. To study BC stemness, we developed a method to purify and amplify BC in vitro from Krox20Cre/+ , R26RYFP/+ mouse embryos. We show that BC progeny are EGF/FGF2-responsive, form spheres, and express neural crest markers. Upon growth factor withdrawal, BC progeny gave rise to multiple neural crest and CNS lineages. Transplanted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
0
48
0
1
Order By: Relevance
“…These cells, and specifically boundary cap cells, which form the border between the developing peripheral and CNS, generate myelinating Schwann cells [229]. Their increased migratory and myelinating properties [230], as well as their potential to also generate myelinating oligodendrocyte [231], make Schwann cells another promising candidate for cell replacement therapy in myelin disorders.…”
Section: Schwann Cellsmentioning
confidence: 99%
“…These cells, and specifically boundary cap cells, which form the border between the developing peripheral and CNS, generate myelinating Schwann cells [229]. Their increased migratory and myelinating properties [230], as well as their potential to also generate myelinating oligodendrocyte [231], make Schwann cells another promising candidate for cell replacement therapy in myelin disorders.…”
Section: Schwann Cellsmentioning
confidence: 99%
“…In addition to this possible role, boundary cap cells can also function as stem cells, and may even be capable of generating CNS cell types including OLs (Zujovic et al 2011), although this has to be confirmed in vivo. Boundary cap cells have not yet been studied in detail in zebrafish but given the suitability of zebrafish for live-cell imaging and lineagebased studies, this is likely to be a very fruitful area of future research.…”
Section: Glial Cell Development and Function In Zebrafishmentioning
confidence: 99%
“…16 bNCSCs are able to generate central glial and neuronal cells in vitro and after transplantation in vivo. [17][18][19] During their differentiation to neurons and glia, bNCSCs also have a unique ability to induce proliferation of insulin producing beta cells and to increase beta cell survival and improve their function in co-culture 20,21 and cotransplantation 22 experiments. However, undifferentiated bNCSCs or their differentiated derivatives do not have beneficial effects on beta cell proliferation and function.…”
Section: Introductionmentioning
confidence: 99%